Formation of single-dominant-species patches of Dicranopteris dichotoma primarily influenced by understory light intensity - Dong, Dubin; Tong, Jiali; Liao, Liang; Yi, Lita; Yan, Wende; Yu, Fei (Frontiers in Plant Science, 2024)
Introduction The Dicranopteris dichotoma fern community plays vital roles in nutrient sequestration, succession regulation, and ecological threshold control. However, the mechanisms underlying the formation of the D. dichotoma–dominant community remain unclear. Methods This study established four different community types to investigate the effects of environmental factors on the formation of a D. dichotoma–dominant community. Results We found that climate was the primary factor affecting the formation of patches dominated by D. dichotoma at the regional scale. Specifically, higher annual mean temperature and annual mean precipitation were associated with larger single-dominant-species patches of D. dichotoma. Understory light intensity was the major factor affecting the formation of the D. dichotoma community at the community scale. Light intensity ranging from 200 to 500 µmol·m⁻²·s⁻¹ was most conducive to the development of a large D. dichotoma community. Additionally, understory light intensity enhanced the importance value of D. dichotoma in the herb community by decreasing its biomass proportion of support modules and increasing its biomass proportion of photosynthetic and reproductive modules. Soil properties and D. dichotoma characteristics showed interactions with each other. Acidic red-yellow soil was most suitable for the formation of single-dominant-species patches of D. dichotoma, and the growth of D. dichotoma further decreased the soil pH. Soil total phosphorus content was identified as a limiting factor for formation of the D. dichotoma community. Discussion In summary, the formation of single-dominant-species patches of D. dichotoma is mainly influenced by a combination of climate, community, and soil.